Neuroplasticity, neurotransmitters and new directions for treatment of anomia in Alzheimer disease. - Falchook, Adam D.; Heilman, Kenneth M.; Finney, Glen R.; Gonzalez-Rothi, Leslie J.; Nadeau, Stephen E. (Aphasiology, 2014)
Background:Anomia is often one of the earliest signs of Alzheimer disease (AD), and progressive language impairment remains a major source of disability throughout the disease course. Aims:This article reviews the potential uses of pharmacological adjuvants to augment neuroplasticity during speech and language therapy. Main Contribution:We begin with a discussion of the nature of anomia in AD from the perspective of classical aphasia models and in terms of a parallel distributed processing model of language. Physiological functions of acetylcholine, norepinephrine and dopamine are reviewed. We consider how pharmacological manipulation of these neurotransmitters in combination with speech and language therapy has the potential to promote maintenance and restoration of the functional connectivity within the lexical, semantic and phonological networks that are the basis of propositional language. Conclusions:AD is a disease of synaptic loss. People with AD are able to reacquire knowledge, and pharmacological modulation of acetylcholine, norepinephrine and dopamine can influence the maintenance and reformation of neuronal networks.